2017
DOI: 10.1111/1440-1681.12700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high‐sodium intake on systemic blood pressure and vascular responses in spontaneously diabetic WBN/Kob‐Leprfa/fa rats

Abstract: SummaryThe prevalence of type 2 diabetes mellitus (T2DM) and hypertension has markedly increased worldwide. The purpose of the present study was to examine the effects of a high‐salt intake on the systolic blood pressure (SBP) and vascular responses in WBN/Kob‐Lepr fa/fa (WBKDF) rats, a new spontaneous animal model of T2DM. Male WBKDF rats and age‐matched Wistar rats at 6 weeks of age were each divided into two groups and fed either a normal‐sodium (NS, 0.26%) diet or high‐sodium (HS, 8%) diet for 14 weeks: (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 35 publications
0
6
1
Order By: Relevance
“…These results suggest that hyperglycemia in the WBKDF rat is mainly due to hyperphagia [ 16 ]. However, our present and previous studies [ 9 ] found no significant differences in food consumption. Thus, inhibition of hyperglycemia by HS intake in WBKDF rats is unlikely due to reduced food and calorie intake.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…These results suggest that hyperglycemia in the WBKDF rat is mainly due to hyperphagia [ 16 ]. However, our present and previous studies [ 9 ] found no significant differences in food consumption. Thus, inhibition of hyperglycemia by HS intake in WBKDF rats is unlikely due to reduced food and calorie intake.…”
Section: Discussioncontrasting
confidence: 93%
“…The male WBKDF rat used in this study is a new metabolic syndrome model exhibiting obesity, dyslipidemia, and T2DM [ 4 6 , 8 ]. Recently, we found that HS intake produces salt-sensitive hypertension in WBKDF rats, suggesting this strain as a useful animal model of metabolic syndrome [ 9 ]. This encouraged us to examine the effects of HS intake on T2DM model rats with salt sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Systolic blood pressure (SBP) was monitored using a tail cuff blood pressure analyzer (BP98A-L, Softron, Tokyo, Japan) as described previously [ 36 ]. The rats were prewarmed for 15–20 min at 32°C to improve the detection of pulsation of the tail artery.…”
Section: Methodsmentioning
confidence: 99%